2002
DOI: 10.1097/00000374-200204000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Treatment Restores Cellular Immunity After Ethanol Exposure and Burn Injury

Abstract: These studies suggest that the loss of lymphocyte production of IL-4 after ethanol exposure and burn injury may contribute to the exaggerated production of IL-6, a known mediator of immune suppression after injury. Moreover, the administration of IL-4 may be beneficial for patients with injuries that are characterized by a dysregulated inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
2
1
0
Order By: Relevance
“…However, a shift in the cytokine response from Th1 to Th2 cannot always be used as a general indicator of immune status after injury, as our laboratory has previously reported immune de- fects that appear later (7-10 days) after injury in the presence of high levels of IFN-␥ [4]. Additionally, using a murine model of burn injury combined with acute ethanol exposure, we observed that IL-4 levels were actually suppressed and that administration of IL-4 to achieve levels similar to sham-injured mice actually restored immunity [43]. It should be noted, however, that the cytokines reported in those studies were induced by pan stimulation of T cells rather than via Agspecific pathways.…”
Section: Discussionsupporting
confidence: 53%
“…However, a shift in the cytokine response from Th1 to Th2 cannot always be used as a general indicator of immune status after injury, as our laboratory has previously reported immune de- fects that appear later (7-10 days) after injury in the presence of high levels of IFN-␥ [4]. Additionally, using a murine model of burn injury combined with acute ethanol exposure, we observed that IL-4 levels were actually suppressed and that administration of IL-4 to achieve levels similar to sham-injured mice actually restored immunity [43]. It should be noted, however, that the cytokines reported in those studies were induced by pan stimulation of T cells rather than via Agspecific pathways.…”
Section: Discussionsupporting
confidence: 53%
“…This study also confirmed that increased levels of CECs correspond to increased levels of proinflammatory cytokines in the acute phase of burn and inhalation injury in relation to the severity of injury and as the patients develop complications or die. As noted in the literature, there was an elevation in plasma levels of IL-10 26,27 and IL-4, 28 anti-inflammatory cytokines, with the increase in the proinflammatory cytokines. As reported by Yeh et al, 29 IL-10 levels were decreased in survivors compared with nonsurvivors.…”
Section: Discussionsupporting
confidence: 58%
“…Although the overall impact of EtOH intoxication on postburn pathogenesis remains to be investigated, a few studies have suggested that the patients who consumed EtOH before injury are more susceptible to infection, exhibit higher morbidity, and are more likely to die than patients who have not consumed EtOH (18,(33)(34)(35)54). Similarly, findings from experimental settings suggest that EtOH intoxication before burn injury exacerbates the suppression of host immune defense, deteriorates intestinal barrier functions, and increases intestinal bacterial translocation (4,6,13,26,28,35,36).…”
mentioning
confidence: 99%